PENGARUH KUALITAS LAYANAN TERHADAP KEPUASAN PELANGGAN YANG DIMEDIASI OLEH KEPERCAYAAN (Studi pada Mahasiswa di LDC FEB UB) - Umaamah ; Sunaryo SE., M.Si., Ph.D (Manajemen FEB - UB, 2018)
The objective of this study on students at LDC FEB UB is to analyze the influence of service quality on customer satisfaction through trust as the mediator variable. This explanatory research explains causal relationship between variables through hypothesis testing. Using purposive sampling method with non-probability sampling technique, 200 people were selected as the respondents. The instruments of this research were assessed using validity and reliability tests. Data analysis and hypothesis testing were conducted using path analysis in PASW, while the mediation test used Sobel test. The results show that service quality has a positive and significant influence on customer satisfaction with a comparatively low mediation of trust. Therefore, LDC FEB UB should maintain indicators of variables that have dominant influence such as tangibles for service quality, friendliness and respect for customer satisfaction, and good reputation for trust. Keywords: service quality, customer satisfaction, trust, LDC FEB UB